Recent advances in the morphological and functional heterogeneity of the biliary epithelium. (May 2013) - Han, Yuyan; Glaser, Shannon; Meng, Fanyin; Francis, Heather; Marzioni, Marco; McDaniel, Kelly; Alvaro, Domenico; Venter, Julie; Carpino, Guido; Onori, Paolo; Gaudio, Eugenio; Alpini, Gianfranco; et al.
This review focuses on the recent advances related to the heterogeneity of different-sized bile ducts with regard to the morphological and phenotypical characteristics, and the differential secretory, apoptotic and proliferative responses of small and large cholangiocytes to gastrointestinal hormones/peptides, neuropeptides and toxins. We describe several in vivo and in vitro models used for evaluating biliary heterogeneity. Subsequently, we discuss the heterogeneous proliferative and apoptotic responses of small and large cholangiocytes to liver injury and the mechanisms regulating the differentiation of small into large (more differentiated) cholangiocytes. Following a discussion on the heterogeneity of stem/progenitor cells in the biliary epithelium, we outline the heterogeneity of bile ducts in human cholangiopathies. After a summary section, we discuss the future perspectives that will further advance the field of the functional heterogeneity of the biliary epithelium.